2012
DOI: 10.1016/j.ijmyco.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug and extensively drug-resistant tuberculosis in Lisbon and Vale do Tejo, Portugal, from 2008 to 2010

Abstract: Tuberculosis (TB) was explicitly recognized as a major global public health problem in the early 1990s and, if it is to be eliminated, it is essential that every country organize control activities in line with its own epidemiological situation. Portugal still remains among the countries with intermediate incidence, with 2756 cases of TB diagnosed in 2009. The incidence of multidrug-resistant (MDR) TB has been decreasing, representing an average of 1.7% of the total number of TB cases, with about 25% of extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Preliminary simulations were performed for July 2005 (period during which one of the worst recent droughts occurred) and a sensitivity analysis to the river flow was done. For this period, the river flow was estimated as 22 m 3 /s based on [38]. These simulations showed that the model results are very sensitive to the river flow, in particular in the upper estuary ( Figure 3).…”
Section: Model Validation For Droughts and Sensitivity Analysesmentioning
confidence: 96%
See 1 more Smart Citation
“…Preliminary simulations were performed for July 2005 (period during which one of the worst recent droughts occurred) and a sensitivity analysis to the river flow was done. For this period, the river flow was estimated as 22 m 3 /s based on [38]. These simulations showed that the model results are very sensitive to the river flow, in particular in the upper estuary ( Figure 3).…”
Section: Model Validation For Droughts and Sensitivity Analysesmentioning
confidence: 96%
“…The adverse impacts of the 2005 drought were more severe for the farmers than in 2012: the drought itself was more severe and the farmers were less prepared to deal with these events. Because data at Almourol are unavailable for this period, the river flow was estimated based on [38] using data measured at Matrena and Tramagal (http://snirh.pt). .…”
Section: Scenarios Setupmentioning
confidence: 99%
“…Besides providing a clinical approach, these centres also aim to monitor these resistant cases, linking the epidemiological survey performed within the community by public health authorities [3] and systematic molecular genotyping performed by the National Reference Laboratory (NRL). Since the Portuguese NRL receives all the strains isolated from all the MDR-TB patients from Portugal (mandatory since 2007) [4], this approach could allow a very good correlation between the genetic and epidemiological information in order to detect both the resistance profiles, as there are possible relationships between strains due to the occurrence of ongoing transmission [5, 6].…”
mentioning
confidence: 99%
“…Os casos de desenvolvimento de resistência a fármacos antituberculosos foram associados a presença de infecção pelo VIH, a qual também eleva os índices de mortalidade, e o tratamento prévio foi identificado como o fator de risco mais forte (MACEDO et al, 2012;OLIVEIRA et al, 2013). Um estudo relatou que o tratamento incompleto, hospitalização por tratamento de TB e reação adversa foram os desfechos relacionados ao tratamento prévio de doentes com tuberculose multirresistente (TBMR) (RIFAT, 2015).…”
Section: Tuberculose Multirresistenteunclassified